Tracheal agenesis as a rare cause of difficult intubation in a newborn with respiratory distress: a case report - Raja Lope Ahmad, Raja Ahmad Al'konee; Abdullah, Kahairi; Mokhtar, Lukman; Abdullah, Ahmad Fadzil (BioMed Central, 2009)
Introduction: Tracheal agenesis is a very rare congenital airway anomaly. It may pose a great challenge to the first attending physician both in diagnosis and in establishing the airway during the first day of life.